Multidisciplinary perinatal management of the compromised airway on placental support: lessons learned. (4th August 2013) - Osborn, Alexander J.; Baud, David; Macarthur, Alison J.; Propst, Evan J.; Forte, Vito; Blaser, Susan M.; Windrim, Rory; Seaward, Gareth; Keunen, Johannes; Shah, Prakesh; Ryan, Greg; Campisi, Paolo
ABSTRACT: Objective: The aims of this study were to review fetal and maternal outcomes after management of the compromised perinatal airway via operation on placental support or ex utero intrapartum treatment and to discuss implications for future management of these complex and rare cases. Methods: We have presented a retrospective case series of 12 neonates requiring airway management on placental support at a single tertiary care, academic center. Results: One mother experienced significant blood loss. Operative recovery times were unremarkable. Eight neonates required airway management due to mass obstruction, two for removal of an endotracheal balloon for fetoscopic treatment of congenital diaphragmatic hernia, one for laryngeal atresia, and one for severe retrognathia. One of our series is an unusual case of management on placental support after vaginal delivery. Another child would have ideally been managed on placental support, but an extremely short umbilical cord prevented this. Even though the airway was secured in all 12 cases, five neonates died in the perinatal period. Conclusions: These procedures have a risk for substantial maternal blood loss. Despite excellent rates of success securing the neonatal airway, children who require management on placental support still have high mortality. A formalized multidisciplinary approach at our institution has enhanced preparedness for these cases. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? The approach to infants with potentially compromised airways requires multidisciplinary planning. Various centers have published their experience with compromised neonatal airway and proposed algorithms regarding its management. Here, we compare our outcomes before and after the institution of a formal multidisciplinary airway management team at the University of Toronto. What does this study add? This is the first paper to examine fetal outcomes before and after the institution of an airway protocol for the infants at risk.